Improved characteristics of HV pulse modulators for technological accelerators - Dolgov, A.; Kildisheva, O. (Вопросы атомной науки и техники, 2004)
The new modulator series intended to provide a pulse power supply of MI-451, MI-456 microwave magnetrons
is described. The main feature of this modulator series, as compared with the existing national counterparts, is the
storage charging power supply. The offered modulators with improved charging power supplies have the substantially better efficiency and high operation stability and reliability. Описано новий ряд модуляторів, призначених для живлення імпульсною потужністю магнетронів MI-
451, MI-456. Запропоновані модулятори мають істотно кращу ефективність, високу стабільність у роботі і
надійність. Описан новый ряд модуляторов, предназначенных для питания импульсной мощностью магнетронов MI-
451, MI-456. Предлагаемые модуляторы имеют существенно лучшую эффективность, высокую стабильность
в работе и надежность.